2018
DOI: 10.1371/journal.pone.0203037
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of circulating T follicular helper cells and regulatory T cells correlating with HIV-1 gp120 variable loop antibodies by a subtype C prophylactic vaccine tested in a Phase I trial in India

Abstract: A Phase I HIV-1 vaccine trial sponsored by the International AIDS Vaccine Initiative (IAVI) was conducted in India in 2009 to test a subtype C prophylactic vaccine in a prime-boost regimen comprising of a DNA prime (ADVAX) and MVA (TBC-M4) boost. The trial demonstrated that the regimen was safe and well tolerated and resulted in enhancement of HIV-specific immune responses. Preliminary observations on vaccine-induced immune responses were limited to analysis of neutralizing antibodies and IFN-γ ELISPOT respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…Since then, subsets of CD4 + T cells with "Tfhlike" characteristics, frequently referred to as circulating Tfh (cTfh) [114][115][116] Patients with autoimmunity such as systemic lupus erythematosus, rheumatoid arthritis, and Sjögren syndrome have increased frequency of cTfh cells with an "activated" phenotype which correlates with disease activity. Since then, subsets of CD4 + T cells with "Tfhlike" characteristics, frequently referred to as circulating Tfh (cTfh) [114][115][116] Patients with autoimmunity such as systemic lupus erythematosus, rheumatoid arthritis, and Sjögren syndrome have increased frequency of cTfh cells with an "activated" phenotype which correlates with disease activity.…”
Section: Tfh Cell S In the B Loodmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, subsets of CD4 + T cells with "Tfhlike" characteristics, frequently referred to as circulating Tfh (cTfh) [114][115][116] Patients with autoimmunity such as systemic lupus erythematosus, rheumatoid arthritis, and Sjögren syndrome have increased frequency of cTfh cells with an "activated" phenotype which correlates with disease activity. Since then, subsets of CD4 + T cells with "Tfhlike" characteristics, frequently referred to as circulating Tfh (cTfh) [114][115][116] Patients with autoimmunity such as systemic lupus erythematosus, rheumatoid arthritis, and Sjögren syndrome have increased frequency of cTfh cells with an "activated" phenotype which correlates with disease activity.…”
Section: Tfh Cell S In the B Loodmentioning
confidence: 99%
“…112,113 Induction of cTfh cells has also been observed in volunteers receiving in-trial HIV vaccines and a novel Escherichia coli vaccine. [114][115][116] Patients with autoimmunity such as systemic lupus erythematosus, rheumatoid arthritis, and Sjögren syndrome have increased frequency of cTfh cells with an "activated" phenotype which correlates with disease activity. [117][118][119][120][121] In HIV-infected individuals, the frequency of CXCR3-cTfh cells correlate with the generation of broadly neutralizing antibody.…”
Section: Tfh Cell S In the B Loodmentioning
confidence: 99%
“…We first evaluated vaccine-induced IFN-γ production using the ELISpot assay and found that vaccination induced significantly higher IFN-γ responses, particularly in response to Env and Gag antigens, clearly indicating that vaccination resulted in successful priming of the immune system. Subsequently we published another report describing in detail the humoral immune responses induced by this vaccine [43]. The magnitude of the IFN-γ response was found to be higher in volunteers who received the heterologous regimen, as compared to those who received the homologous regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Although cell mediated immune responses were not preferentially expanded in Group B participants, we reported in an earlier study that vaccination resulted in a strong induction of antibodies targeting the variable regions of HIV-1gp120, which correlated positively with induction of long-lasting plasma B cells and T Follicular Helper cells in volunteers who received only MVA [43]. Interesting observations of HIV-specific antibodies targeting the rgp41 Env, rgp140 Env, p24 Gag, and rgp120 Env were also made in the P002 trial conducted at UK with the same vaccine constructs [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we examined vaccine-induced humoral and cell-mediated responses to the same subtype C HIV-1 vaccine (ADVAX DNA prime and MVA boost) tested in a phase I clinical trial in India (P001 trial) and reported encouraging findings [30,31]. In the current study, we investigated vaccine-induced peripheral T SCM cells and in vitro viral inhibitory capacity of vaccine-induced CD8 + T cells in the same cohort.…”
Section: Competing Interests: No Authors Have Competing Interestsmentioning
confidence: 98%